Annual Plan 1999-2000 A Supplement of Volume II Statements III Schemewise Outlays and Expenditure Uttar Pradesh - Planning Commission (Planning Commission, 1999)
Agriculture & Allied Activities, Rural Development, Irrigation and Flood Control, Energy, Industry and Minerals, Transport, Communication (No Programme in State Plan), Science Technology and Environment, General Economic Services, Education, Medical and Public Health, Water Supply, Sanitation, Housing and Urban Development, Information and Publicity, Welfare of SC/ST and Other Backward Classes, Labour and Employment, Social Security and Welfare and Nutrition, General Services.
Government of Uttar Pradesh, State Planning Commission